(untitled) (Asia Pacific Journal of Social Innovation, 2024)
Women are underrepresented in STEM related careers. Factors relating to this gender gap can be traced back further ar to how women perceive STEM during their basic education years. This study aims to investigate the effect of a Lego Mindstorm robotics program to high school girls’ aptitude and attitude towards STEM in the Philippines. Forty-nine (49) female grade 10 students (mean age= 16) from a science-based curriculum high school participated in this study. Qualitative and quantitative assesments were used to measure the effectiveness of this robotics program. Quantitatively, assessments on the aptitude of the students, tests on gear knowledge, sensors, and computer programming, and Test of Science Related Attitudes and STEM career Interest Survey were used. Qualitative assessment was done-by thematic analysis of individual journals written by the students during the course of the robotics program. Results indicated that the students’ aptitude significantly improved after the robotics program. Moreover, girls’ attitude cowards STEM did not change significantly after the program. However, the students highly expressed interest towards robotics through their journal entries. A highly correlation was see. Between enjoyment of science business career interest in sciences and between altitudes toward technology and aptitudes toward engineering. The paper discussed some implications and presented recommendations for the furtherance of the study.